The Green School Movement is Promoting Food Security Through Hydroponics at SMP Negeri 1 Rancaekek - Iwan Shalahuddin; Udin Rosidin; Sandra Pebrianti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Indonesia is an agrarian country where practically every area may open agricultural land to grow crops for all sorts of agricultural goods. Food security is one of the important challenges in a country's growth. To accomplish food security. Green schools serve as both educational institutions and forums for raising awareness about the necessity of environmental protection and food sustainability. The objective of the service is to teach students about the necessity of conserving the environment via the use of sustainable agriculture technologies. The technique is structured in four stages: educational approach, learning process, direct practice, and evaluation of results. The outcomes of the service and socialization aimed at 135 junior high school students in grades 7 to 9, offering a grasp of the basic ideas, benefits, and advantages of growing using hydroponic media. Explain how to manufacture hydroponic planting media in detail, emphasizing how hydroponics can be a solution to land constraints while contributing to food security. Conclusion on the application of the concept of green schools that incorporate hydroponic technology, which is a strategic step toward increasing food security, particularly in the educational setting. Green schools serve not only as a place of learning, but also as a hub for innovation and empowerment of the younger generation.